Integration of Ethnoscience in Natural Science learning: Literacy Study - Sudirman Sudirman; Sutikno Sutikno; Dyah Rini Indriyanti; Woro Sumarni; Margareta Rahayuningsi (Jurnal Penelitian Pendidikan IPA, 2025)
Science education is essential for developing scientific literacy and critical thinking. However, traditional approaches often lack contextual relevance, especially in areas rich in local wisdom. This study aims to examine how ethnoscience—science learning that integrates local cultural values—can enhance meaningful learning while preserving cultural identity. The objective is to analyze its application, identify potential local cultural topics, and evaluate effective teaching methods. This qualitative research is conducted through a literature review following the PRISMA framework. From 98 articles identified via the Scopus database, 27 were selected for in-depth analysis. Data were analyzed using thematic content analysis. Results show that 55.56% of the studies used interdisciplinary approaches, while Biology topics were underrepresented (7.40%). Physics and Chemistry showed high contextual relevance, particularly in traditional technologies and natural materials. Common local cultural themes include crafts, martial arts, measurement tools, games, traditional medicine, and eco-friendly pesticides. Media used include modules, digital worksheets, LMS, and interactive technology. Effective pedagogical models include Ethno-STEM, EthCBL, RE-STEM, E-PjBL, and SIL, all of which promote scientific literacy, 21st-century competencies, and cultural appreciation. The findings highlight the potential of ethnoscience to support holistic and culturally responsive science education.